Faktor Budaya Batak dengan Kejadian Stunting - Wahyu, Afnijar; Sagala, Lam Murni; Sinaga, Regina Marintan (Journal of Telenursing (JOTING), 2023)
This research aims to analyze Batak cultural factors with the incidence of stunting. The research method used was an observational design with case-control. This study's results show a relationship between the history of giving breast milk p-value of 0.031, giving colostrum p-value 0.045, and the age of giving MP-ASI p-value of 0.060 with the incidence of stunting in the Batak tribe. There is no relationship between the frequency of giving MP-ASI p-value 0.249 and the incidence of checking in the Batak tribe. In conclusion, Batak cultural factors are related to the incidence of stunting and can be seen in parenting patterns that provide nutrition. Keywords: Culture, Stunting, Batak Tribe